Culture in a post-secular context theological possibilities in Milbank, Barth and Bediako - Thomson, Alan (Cambridge : James Clarke, 2014)
Is culture a theologically neutral concept? The contemporary experts on culture-anthropologists and sociologists-argue that it is. Theologians and missiologists would seem to agree, given the extent of their reliance on anthropological and sociological definitions of culture. Yet this appears a strange reliance given that presumed neutrality in the sciences is a consistently challenged assumption. It is stranger still given that so much theological energy has been expended on understanding and defining the human person in specifically theological as opposed to anthropological terms when cultur.
Front cover; Half title; Title page; Copyright; Contents; Preface; Acknowledgments; List of Abbreviations; Introduction; 1. Theology and the Neutrality of Culture; 2. Challenging the Neutrality of Culture; 3. John Milbank and a Theological Account of Culture; 4. Milbank, Violence, and Idealization; 5. Karl Barth and a Theological Alternative; 6. Kwame Bediako and an African Alternative; Conclusion; Bibliography; Back cover.
Includes bibliographical references and index.
CIP data; item not viewed.
Master record variable field(s) change: 072
Keywords: Christianity and culture; Christianity and culture -- History of doctrines -- 19th century; Christianity and culture -- History of doctrines -- 20th century; Postmodern theology; RELIGION -- Christian Life -- Social Issues; RELIGION -- Christianity -- General; Christianity and culture; RELIGION / Christian Theology / Anthropology; Electronic books